The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1017/ipm.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and treatment of eating disorders in Ireland: healthcare professionals’ knowledge and attitudes

Abstract: Objectives. This study examines aspects of healthcare professionals' knowledge and attitudes about eating disorders (EDs), which might impede the effective detection or treatment of EDs in Ireland.Methods. A total of 1,916 healthcare professionals were invited to participate in a web-based survey. Participants were randomly allocated to view one of five vignettes depicting a young person with symptoms consistent with anorexia nervosa, bulimia nervosa, binge-eating disorder, depression or type 1 diabetes. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…This provides confidence that the research is not biased or unrepresentative. The validity of the results is also supported by their correspondence with previous similar research with adult samples (Griffiths et al, 2014b;McNicholas, O'Connor, O'Hara, & McNamara, 2015;Roehrig & McLean, 2010;Stewart et al, 2006Stewart et al, , 2008. Further research is necessary to discern the potential effects of participant characteristics (e.g., gender and personal eating or weight concerns), which would help tailor and target destigmatisation initiatives.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This provides confidence that the research is not biased or unrepresentative. The validity of the results is also supported by their correspondence with previous similar research with adult samples (Griffiths et al, 2014b;McNicholas, O'Connor, O'Hara, & McNamara, 2015;Roehrig & McLean, 2010;Stewart et al, 2006Stewart et al, , 2008. Further research is necessary to discern the potential effects of participant characteristics (e.g., gender and personal eating or weight concerns), which would help tailor and target destigmatisation initiatives.…”
Section: Discussionsupporting
confidence: 73%
“…One such factor is the name given to the vignette target. A similar study previously conducted with health professionals, which also asked participants to judge the gender of the vignette target, reported gender judgements that were more male-oriented than in the current study (McNicholas et al, 2015). The difference can be attributed to the previous study's use of the name 'Morgan', which in national naming conventions is more heavily skewed towards males than 'Alex' (Central Statistics Office, 2015).…”
Section: Discussionmentioning
confidence: 40%
“…Knowledge and stigma did not necessarily improve together. This is also evident in samples of professionals, who have higher levels of knowledge but may retain stigmatizing attitudes (McNicholas et al, ), highlighting that stigma and knowledge are distinct domains. Those wishing to plan stigma reduction interventions should bear this in mind.…”
Section: Discussionmentioning
confidence: 94%
“…There is a strong correlation between eating disorder training and comfort level in identifying and managing eating disorders [29] [30]. Increased knowledge and screening results in early detection and intervention by physicians [27][31] [32]. Yet, medical providers may still lack the training and confidence to intervene.…”
Section: Physiciansmentioning
confidence: 99%
“…Yet, medical providers may still lack the training and confidence to intervene. To illustrate, McNicholas et al [27] discovered that only 14.9% of physician respondents felt confident in their ability to manage eating disorders. Similarly, Linville et al [32] found 78% of medical providers were unsure of how to treat eating disorders, 92% felt they missed a diagnosis, and 67% reported a need for continuing education.…”
Section: Physiciansmentioning
confidence: 99%